2014
DOI: 10.1002/jqs.2698
|View full text |Cite
|
Sign up to set email alerts
|

Multiproxy diet analysis of the last meal of an early Holocene Yakutian bison

Abstract: General rightsThis document is made available in accordance with publisher policies. Please cite only the published version using the reference above. Full terms of use are available: http://www.bristol.ac.uk/pure/about/ebr-terms AbstractPollen, botanical macrofossils, chemical components and ancient DNA were studied in samples from the rumen of a frozen Yakutian bison (Bison priscus) that lived ca. 10,500 calendar years before present. The dialkyl glycerol ether lipid archaeol (2,3-di-O-phytanyl-sn-glycerol)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…The priors for the analyses (other than default) were: relaxed uncorrelated lognormal clock (estimated); Yule process of speciation; and a random starting tree. To this analysis, we included a rbcL partial paleosequence (137 bp) found in the rumen of a Holocene Yakutian bison (Bison priscus) that was radiocarbon dated to about 10,500 cal a BP (Van Geel et al, 2014). This estimate was not applied for molecular clock calibration as the bison age is too recent.…”
Section: Molecular Clock Approachmentioning
confidence: 99%
“…The priors for the analyses (other than default) were: relaxed uncorrelated lognormal clock (estimated); Yule process of speciation; and a random starting tree. To this analysis, we included a rbcL partial paleosequence (137 bp) found in the rumen of a Holocene Yakutian bison (Bison priscus) that was radiocarbon dated to about 10,500 cal a BP (Van Geel et al, 2014). This estimate was not applied for molecular clock calibration as the bison age is too recent.…”
Section: Molecular Clock Approachmentioning
confidence: 99%
“…PalEnDNA from coprolites and preserved gut contents has been used to reconstruct palaeodiets of extinct fauna, particularly woolly mammoth, bison and the moa, a large, flightless New Zealand ratite bird (van Geel et al ., , , ; Wood et al ., , , , , ). PalEnDNA from coprolites also contains information about parasite faunas, including those of extinct species.…”
Section: Progress In the Use Of Palendna In Quaternary And Archaeologmentioning
confidence: 99%
“…Multidisciplinary and multiproxy approaches to Quaternary and archaeological research have been shown to improve palaeoenvironmental reconstructions (e.g. Newnham et al ., ; Birks and Birks, ; Birks et al ., ; Jørgensen et al ., ; Wood et al ., ; Parducci et al ., ; van Geel et al ., ). aDNA analyses, including PalEnDNA studies, should not be viewed as replacing more traditional techniques, such as studies of plant macrofossils and pollen, but rather as a complementary tool generating both overlapping and separate results (e.g.…”
Section: Recommendations For Future Palendna‐based Researchmentioning
confidence: 99%
“…The geological context of lakes provides a robust archive for the retrieval of ancient plant DNA through time and reflects the effect of all environments worldwide (Willerslev, 2003 ; Bremond et al, 2017 ; Parducci et al, 2017 ). Plant residues can also be found in ancient animal and human remains such as palaeofaeces, hair, dental calculus, and gastrointestinal contents (Poinar et al, 2001 ; Rawlence et al, 2014 ; Van Geel et al, 2014 ; Weyrich et al, 2015 ).…”
Section: Looking For Ancient Plant Dnamentioning
confidence: 99%